Component-based software development for report generation - Tan, Wan Ling. (2008)
This project explores on the computer-based report generation through the use of the Data Flow Net. It treats the processing details for generating reports as processing components. Consequently, common processing details for generating reports can be reused and composed in a program for reporting printing.